1987
DOI: 10.1083/jcb.105.6.2763
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical localization of myosin heavy chain isoforms and paramyosin in developmentally and structurally diverse muscle cell types of the nematode Caenorhabditis elegans.

Abstract: Abstract. The nematode Caenorhabditis elegans contains two major groups of muscle cells that exhibit organized sarcomeres: the body wall and pharyngeal muscles. Several additional groups of muscle cells of more limited mass and spatial distribution include the vulval muscles of hermaphrodites, the male sex muscles, the anal-intestinal muscles, and the gonadal sheath of the hermaphrodite. These muscle groups do not exhibit sarcomeres and therefore may be considered smooth. Each muscle cell has been shown to hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
105
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 120 publications
(111 citation statements)
references
References 37 publications
6
105
0
Order By: Relevance
“…As reported previously (Ardizzi and Epstein, 1987), MYO-3 myosin heavy chain A (myoA; Fig. 2A-C) and UNC-15 paramyosin ( Fig.…”
Section: Expression Patterns Of Cytoskeletal Proteins In the C Elegasupporting
confidence: 85%
See 4 more Smart Citations
“…As reported previously (Ardizzi and Epstein, 1987), MYO-3 myosin heavy chain A (myoA; Fig. 2A-C) and UNC-15 paramyosin ( Fig.…”
Section: Expression Patterns Of Cytoskeletal Proteins In the C Elegasupporting
confidence: 85%
“…Previous studies by others have shown that the myoepithelial sheath cells express MYO-3 (myoA; Fig. 4A-C) and UNC-54 (myoB) myosin heavy chains (Ardizzi and Epstein, 1987) that are also expressed in the striated body wall muscle and that UNC-54 localizes to the outer regions, whereas MYO-3 is limited to the central part of the thick filaments (Rose et al, 1997) as observed in the thick filaments in the striated body wall muscle (Miller et al, 1983). UNC-15 paramyosin was also expressed in the myoepithelial sheath (Ardizzi and Epstein, 1987;Fig.…”
Section: Thick Filamentsmentioning
confidence: 80%
See 3 more Smart Citations